Рецепция творчества П.Д. Боборыкина в критике и литературоведении - Петренко, Н.А. (Культура народов Причерноморья, 2013)
В статье рассматриваются интерпретации творчества П.Д. Боборыкина в русской
критике и литературоведении второй половины XIX – начала XXI вв. Выясняются причины
неоднозначного, стереотипного восприятия художественных произведений писателя.
Ключевые слова: рецепция, художественный метод, натурализм, реализм, психологизм. У статті розглядаються інтерпретації творчості П.Д. Боборикіна в російській критиці та
літературознавстві другої половини ХІХ – початку ХХІ ст. З’ясовуються причини неоднозначного,
стереотипного сприйняття художніх творів письменника.
Ключові слова: рецепція, художній метод, натуралізм, реалізм, психологізм. The article deals with the interpretation of creation P.D. Boborykin in Russian literary criticism, in
the second half of XIX – beginning of XXI century. The causes of ambiguous stereotypes of the writer’s creation
are established there. It is noted that P.D. Boborykin’s works from the first day of publication have been
appeared at the center of an acute literary polemics, became the object of heated debate, have been causing
enthusiastic acclaim from ones (S.A. Vengerov, M.A. Protopopoff, M.K. Tsebrikovа, K.F. Golovin, V.E.
Cheshikhin) and misunderstanding of others (D.D. Minaev, Mikhail Saltykov-Shchedrin, P.N. Tkachev, A.V.
Nikitenko). A merit of «rehabilitation» of creativity Boborykin is belongs to such researchers of XX – XXI
centuries (T.P. Den, V.B. Smirnov, V.I. Samusenko, E.I. Romanova, N.A. Kolosova, V.B. Kataev, S.I. Scheblykin,
O.A. Meleshkova etc.). They consider the genre originality of the writer, especially its style and originality of the
characters which he portrays.
Key words: reception, an artistic technique, naturalism, realism, psychologism.